Is the partial pressure of carbon dioxide in the blood related to the development of retinopathy of prematurity?. Issue 9 (1st September 2001) - Gellen, Balazs; McIntosh, Neil; McColm, Janet R; Fleck, Brian W
Abstract : AIMS: To determine the role of carbon dioxide in the development of retinopathy of prematurity (ROP). METHODS: This was a retrospective cohort study of 25 consecutive infants admitted to the neonatal unit with continuously recorded physiological data. The daily mean and standard deviation (SD) of transcutaneous carbon dioxide partial pressure (tcPco 2 ) was compared between infants who had stage 1 or 2 ROP and stage 3 ROP. The time spent hypocarbic (<3 kPa) and/or hypercarbic (>10 kPa and >12 kPa) was also compared between these groups. Intermittent arterial carbon dioxide tension was also measured and compared with the simultaneous tcPco 2 data. RESULTS: There were no significant differences in carbon dioxide variability or time spent hypocarbic and/or hypercarbic between the ROP groups on any day. 86% of transcutaneous values were within 1.5 kPa of the simultaneous arterial value. CONCLUSION: TcPco 2 measurement can be a very useful management technique. However, in this cohort neither variable blood carbon dioxide tension nor duration of hypercarbia or hypocarbia in the first 2 weeks of life was associated with the development or severity of ROP.